Characterization of screen printed and fire-through contacts on LPCVD based passivating contacts in monoPoly™ solar cells. (15th May 2020) - Padhamnath, Pradeep; Buatis, Jammaal Kitz; Khanna, Ankit; Nampalli, Nitin; Nandakumar, Naomi; Shanmugam, Vinodh; Aberle, Armin G.; Duttagupta, Shubham
Graphical abstract: Plots showing the specific contact resistance (left) and the recombination current under the metal fingers (right) for three different metallization pastes for two different thickness of poly-Si. An ideal paste should exhibit both lower contact resisitivity and lower recombination current density. Highlights: Ideal metal paste should to both low contact resistance and recombination current density. Small sized and densely spread metal crystallites result in excellent contact resistivity. Thinner layers boost the cell current and efficiencies, if the passivation quality is maintained. Excellent contact resistivity of ~1 mΩ cm 2 and recombination current density under metal contacts of 30 ± 5 fA/cm 2 . Abstract: In this work we have characterized screen-printed passivating contacts formed by different commercially available fire-through pastes on phosphorus doped ( n + ) polysilicon (poly-Si) layers at the rear side of monoPoly™ solar cells. Extremely low recombination current density under metal contacts ( J01, metal ) of 35–45 fA/cm 2 and excellent specific contact resistivity ( ρc ) values of ~ 1.3 mΩ-cm 2 are obtained for two different thicknesses of poly-Si (150 nm and 250 nm) used in this work. We demonstrate that, although the metal induced recombination increases with reducing thickness of the poly-Si layer, thinner poly-Si layers can lead to higher efficiencies on account of reduced parasitic absorption leading to higher cell current. A champion efficiency of 22.6% is reported for busbarless monoPoly™ cells with the best performing fire-through (FT) paste on large area (244.3 cm 2 ) commercially available Czochralski grown Si wafers.